The Analysis of Implementing STEM-based LKPD to Enhance Students’ Collaboration Skills in School - Putri, Rifani Septya; Hendri, Menza; Rasmi, Dian Pratiwi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
This research focused on applying STEM-based LKPD to improve students’ collaboration skills in schools. The aim is to determine whether STEM-based LKPD can improve students’ collaboration skills at school. The method used is literature research by taking a literature review following the subject matter and analyzing it in depth to draw conclusions and findings. Based on a review of several literature sources and relevant research findings, the following conclusions are drawn: (1) the implementation of STEM-based instructional materials (LKPD) is effective in improving students’ collaboration skills in science learning; (2) STEM learning can be integrated with various instructional models such as Project Based Learning, Problem-Based Learning, and cooperative learning models; (3) STEM-based instructional materials can be implemented in schools, ranging from elementary to high school levels.